Rancang Bangun Sistem Parkir Menggunakan Kartu Barcode di Pasar Setono Betek Kediri - Wenesdy Fajar Ega Roosdwita; Agung Priyanto; Ari Cahyono; Nurul Fatimah (Fakultas Teknik dan Teknologi Informasi, Universitas Jenderal Achmad Yani Yogyakarta, 2020)
Along with the development of technology and information, human needs are increasing. Especially now that the parking system has experienced rapid development with a level of security for vehicles. One of the important things is the parking problem, the parking problem where the parking lot is large enough but still not supported by an adequate system. The use of a manual parking system has now begun to shift now with an automatic parking system that is integrated with the database as part of the parking system. Barcode card is a code in the form of a line of black or rectangular lines. Each line of the rectangle has a different width. So in this study the barcode card is used as an ID for parking users or parking customers who replace the manual parking system. The parking system data collection starts with Barcode Card user parking which is invincible with the parking user database via Barcode Scan. In a parking system using a Barcode Card, parking users can see the hours of entry and exit of parking congestion. by simply scanning or pasting the Barcode Card on the HC-SR04 sensor. This parking system will work based on existing data on the RFID tag and RFID reader. The data from the RFID tag will read the RFID reader and be processed in the Raspberry pi and servo motor to open and close the bar, then the buzzer will sound after which the ultrasonic sensor closes and opens the bar when the motor passes the sensor. With the parking system using this Barcode Card can provide security, comfort in the parking area is more guaranteed, and the parking area is managed in an orderly manner.